Negative electrode active material, secondary battery and electronic device

By designing the elongated negative electrode active material and adjusting its arrangement on the current collector, the problems of expansion and energy density of lithium-ion batteries during circulation are solved, and high energy density and safety performance are achieved.

CN114975996BActive Publication Date: 2025-01-07NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210578840.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-01-07
Estimated Expiration
2041-06-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have high expansion requirements during circulation, making it difficult to take into account high energy density, cycle life and safety performance.

Method used

A special negative electrode active material is used, and its particles have an elongated morphology, with a width-length ratio of 0.1≤AR10<0.2, 0.2≤AR50<0.4, 0.4≤AR90≤0.8, and the angle between the particle length and current collector is 45° ≤θ≤90° to increase the embedded and disengagement speed of lithium ions, and adjust the particle arrangement through magnetic field treatment to control expansion.

Benefits of technology

It significantly improves the rate performance and circulation performance of lithium-ion batteries, reduces the expansion of the negative electrode, and enhances the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114975996B_ABST
    Figure CN114975996B_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode active material, a secondary battery and an electronic device, wherein the negative electrode active material particles satisfy the following relationship: 0.1≤AR 10 <0.2,0.2≤AR 50 <0.4, where the width-to-length ratio of the negative electrode active material is AR when the particle volume cumulative distribution is 10% 10 When the particle volume cumulative distribution is 50%, the width-to-length ratio of the negative electrode active material is AR 50 The lithium-ion battery including the negative electrode active material of the present application can meet the requirements of safety, cycle and cycle expansion while ensuring high energy density performance (capacity, first efficiency, compaction density).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application date June 21, 2021, application number 202110687403.8, and invention name “Negative electrode active materials, secondary batteries and electronic devices”. Technical Field

[0002] The present application relates to the field of energy storage technology, and in particular to a negative electrode active material, a secondary battery and an electronic device. Background Art

[0003] The lithium-ion battery industry has entered a period of rapid growth, and the scale of the industry has grown rapidly. As a new type of high-energy green battery, lithium-ion batteries are widely used in notebook computers, mobile phones, new energy electric vehicles and other fields. This has put forward higher requirements for lithium-ion battery energy density, cycle life, cost and safety. Ensuring safety performance can enhance product competitiveness. Improving energy density performance can increase battery life, thereby improving the comfort of user experience.

[0004] As mobile phones, notebooks and other electronic devices become thinner, the requirements for battery expansion during the cycle process are getting higher and higher. How to reasonably design a negative electrode to obtain a lithium-ion secondary battery that takes into account high energy density performance (capacity, initial efficiency, compaction density), cycle life and safety performance is a common problem faced by the industry. Summary of the invention

[0005] The present application attempts to solve at least one problem existing in the related art to at least some extent by providing a negative electrode active material and a secondary battery and an electronic device using the same.

[0006] According to the first aspect of the present application, the present application provides a negative electrode active material, wherein the negative electrode active material particles satisfy the following relationship: 0.1≤AR 10 <0.2,0.2≤AR 50 <0.4, where the width-to-length ratio of the negative electrode active material is AR when the particle volume cumulative distribution is 10% 10 When the particle volume cumulative distribution is 50%, the width-to-length ratio of the negative electrode active material is AR 50 .

[0007] According to some embodiments of the present application, the negative electrode active material satisfies 0.4≤AR 90 ≤0.8, AR 90 It indicates the width-to-length ratio of the negative electrode active material when the cumulative distribution of particle volume is 90% in the particle size distribution. The negative electrode active material within the above range has a high proportion of elongated particles, which can accelerate the rapid deintercalation of lithium ions and improve the rate performance of secondary batteries.

[0008] According to some embodiments of the present application, 1.3 < AR 90 / AR 50 <3.5. Controlling the distribution of the aspect ratio of the negative electrode active material particles within this range can further increase the speed of lithium ion insertion and extraction, improve the rate performance of the secondary battery, and improve the deformation of the negative electrode.

[0009] According to some embodiments of the present application, the negative electrode active material satisfies at least one of the conditions (a) to (d): (a) the negative electrode active material satisfies 1.5≤Dv99 / Dv50≤4.5; (b) the gram capacity of the negative electrode active material is ≥355mAh / g; (c) the ratio of the diffraction peak area C004 of the 004 crystal plane of the negative electrode active material to the diffraction peak area C110 of the 110 crystal plane satisfies 10≤C004 / C110≤40; (d) the compaction density of the negative electrode active material is ≥1.90g / cm 3 .

[0010] According to some embodiments of the present application, the negative electrode active material satisfies 1.5≤Dv99 / Dv50≤4.5. In the present application, since the particle major diameter is arranged perpendicular to the current collector, when the particle size of the negative electrode active material is too large, the prepared negative electrode is prone to produce convex points on the surface of the negative electrode active material layer after a certain pressure treatment. The convex points will affect the appearance of the negative electrode pole piece on the one hand, and on the other hand, it is easy to precipitate lithium, affecting the cycle performance of the battery, and the particles are too large, which is not conducive to the insertion and extraction of lithium ions. According to some embodiments of the present application, the ratio of the diffraction peak area C004 of the 004 crystal plane to the diffraction peak area C110 of the 110 crystal plane of the negative electrode active material satisfies 10≤C004 / C110≤40. The C004 / C110 of the negative electrode active material is within the above range, which is more conducive to the insertion and extraction of lithium ions.

[0011] According to some embodiments of the present application, the compaction density of the negative electrode active material is ≥1.90 g / cm 3 The compaction density of the negative electrode active material is related to the pressure that the negative electrode material can withstand after being prepared into the negative electrode. Materials with high compaction density are conducive to the preparation of batteries with high volume energy density.

[0012] According to some embodiments of the present application, the negative electrode active material includes artificial graphite.

[0013] In some embodiments of the present application, the artificial graphite includes at least one of needle coke artificial graphite, petroleum coke artificial graphite or asphalt artificial graphite.

[0014] According to the second aspect of the present application, the present application provides a secondary battery, which includes a positive electrode, a separator, an electrolyte and a negative electrode, wherein the negative electrode includes a negative electrode collector and a negative electrode active material layer, and the negative electrode active material layer includes the negative electrode active material described in the first aspect.

[0015] According to some embodiments of the present application, the negative electrode comprises negative electrode active material particles whose angle θ between the long axis direction and the negative electrode current collector satisfies 45°≤θ≤90°. According to some embodiments of the present application, in the negative electrode, the negative electrode active material particles are as follows: Figure 1 As shown in the figure, the long diameter is arranged on the current collector at a certain angle, and the angle of arrangement is ≥45°. In this way, the path of lithium ions being inserted into the negative electrode active material layer is greatly shortened during the lithium insertion process, which can effectively increase the lithium insertion speed. At the same time, during the lithium insertion process, since the acute angle between the long diameter and the current collector is ≥45°, Figure 2 As shown, lithium ions are embedded into the negative electrode active material layer from the short axis direction, so the expansion perpendicular to the negative electrode direction is greatly reduced.

[0016] In some embodiments of the present application, the negative electrode comprises negative electrode active material particles whose angle θ between the long axis and the current collector satisfies 55°≤θ≤85°. According to some embodiments of the present application, in the negative electrode active material layer, the angle θ between the long axis of the negative electrode active material and the negative electrode current collector satisfies 45°≤θ≤90°.

[0017] According to some embodiments of the present application, in the negative electrode active material layer, an angle θ between the long axis direction of the negative electrode active material and the negative electrode current collector satisfies 55°≤θ≤85°.

[0018] According to some embodiments of the present application, the negative electrode satisfies at least one of the conditions (e) to (f): (e) the ratio of the diffraction peak area C004 of the 004 crystal plane to the diffraction peak area C004 of the 110 crystal plane of the negative electrode satisfies C004 / C110≤15; (f) the electrolyte infiltration time of the negative electrode is ≤2min. The C004 / C110 of the negative electrode is more conducive to the insertion and extraction of lithium ions within the above range.

[0019] According to a third aspect of the present application, the present application provides an electronic device, which includes the secondary battery described in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the arrangement of negative electrode active materials on the current collector according to an embodiment of the present application.

[0021] Figure 2 Schematic diagram of lithium ion embedding into graphite layer of negative electrode according to an embodiment of the present application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present application and the embodiments given belong to the scope of protection of the present application.

[0023] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0024] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0025] In order to ensure high energy density performance (capacity, first efficiency, compaction density) while meeting safety, cycle and cycle expansion, this application, on the one hand, selects easily graphitized precursors to increase the gram capacity of the negative electrode active material to meet the energy density requirements. On the other hand, the morphology of the negative electrode active material particles is controlled to be slender, and magnetization technology is used to arrange the particles in a certain direction on the current collector. This can control the expansion of the negative electrode plate while obtaining high energy density, thereby greatly improving the rapid charging and discharging performance of lithium-ion batteries.

[0026] 1. Negative electrode active materials

[0027] The present application provides a negative electrode active material, wherein the negative electrode active material satisfies the following relationship: 0.1≤AR 10 <0.2,0.2≤AR 50 <0.4, where the width-to-length ratio of the negative electrode active material is AR when the particle volume cumulative distribution is 10% 10 When the particle volume cumulative distribution is 50%, the width-to-length ratio of the negative electrode active material is AR 50 .

[0028] As used herein, the "width-to-length ratio" of a negative electrode active material refers to the ratio of the wide diameter to the long diameter of the negative electrode active material particles. The width-to-length ratio of the negative electrode active material can be obtained by dynamic particle image analysis (for example, using a Sympatec QICPIC dynamic particle image analyzer). The "wide diameter" of a negative electrode active material particle refers to the minimum value between parallel lines tangent to the projected image of the particle. The "long diameter" of a negative electrode active material particle refers to the maximum value between parallel lines tangent to the projected image of the particle. When the width-to-length ratio of the negative electrode active material is small, the negative electrode active material particles are elongated in shape.

[0029] As used herein, “AR n " refers to the width-to-length ratio of the negative electrode active material particles when the cumulative volume distribution of the negative electrode active material particles is n%. "AR 10 "AR" represents the width-to-length ratio of the negative electrode active material particles when the cumulative volume distribution of the negative electrode active material particles is 10%. 50 "AR" represents the width-to-length ratio of the negative electrode active material particles when the cumulative volume distribution of the negative electrode active material particles is 50%. 90 ” represents the width-to-length ratio of the negative electrode active material particles when the cumulative volume distribution of the negative electrode active material particles is 90%.

[0030] According to some embodiments of the present application, the negative electrode active material includes primary particles.

[0031] According to some embodiments of the present application, AR 10 It can be 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 and any value therebetween. In some embodiments of the present application, AR 50 It can be 0.22, 0.24, 0.26, 0.28, 0.30, 0.31, 0.33, 0.35, 0.39 and any value therebetween.

[0032] According to some embodiments of the present application, the negative electrode active material satisfies 0.4≤AR 90 ≤0.8, AR 90 In some embodiments of the present application, AR represents the width-to-length ratio of the negative electrode active material when the cumulative volume distribution of the particles is 90%. 90 It can be 0.45, 0.48, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.70, 0.75 and any value therebetween. Within this range, the proportion of elongated particles in the negative electrode active material is relatively high, which can accelerate the rapid insertion and extraction of lithium ions and improve the rate performance of the secondary battery.

[0033] According to some embodiments of the present application, the negative electrode active material satisfies 1.3<AR 90 / AR 50 <3.5. In some embodiments of the present application, AR 90 / AR 50 The ratio of the width to length of the negative electrode active material particles can be 1.4, 1.5, 1.7, 1.9, 2.0, 2.3, 2.5, 2.7, 2.9, 3.0, 3.2, 3.5 and any value therebetween. Controlling the distribution of the width to length ratio of the negative electrode active material particles within this range can further increase the speed of lithium ion insertion and extraction, improve the rate performance of the secondary battery, and improve the deformation of the negative electrode.

[0034] The aspect ratio distribution of the negative electrode active material of the present application satisfies 0.1≤AR 10 <0.2,0.2≤AR 50 <0.4,0.4≤AR 90 When the angle is ≤0.8, most of the prepared negative electrode active material particles are slender, and the gram capacity of the negative electrode active material is high within this range. When the long diameter of the negative electrode active material particles is 45° to 90° with the direction parallel to the current collector, the transmission path during lithium ion transmission can be reduced, the rapid deintercalation of lithium ions can be accelerated, and the stress on the negative electrode active material particles during the process of lithium ion insertion and deintercalation can be uniformly released in all directions to achieve the effect of improving deformation.

[0035] According to some embodiments of the present application, the negative electrode active material satisfies 1.5≤Dv99 / Dv50≤4.5. In some embodiments of the present application, Dv99 / Dv50 can be 1.8, 2.0, 2.2, 2.5, 2.7, 3.0, 3.3, 3.5, 3.8, 4.0, 4.3 and any value therebetween. In the present application, when the long diameter of the negative electrode active material particles is arranged perpendicular to the current collector and the particle size is too large, the prepared negative electrode is prone to produce convex points on the surface of the negative electrode active material layer after a certain pressure treatment. The convex points will affect the appearance of the negative electrode pole piece on the one hand, and on the other hand, it is easy to precipitate lithium and affect the cycle performance of the battery. And the particles are too large, which is not conducive to the embedding and extraction of lithium ions. Therefore, it is necessary to control the particle size of the negative electrode active material particles within the above range.

[0036] According to some embodiments of the present application, the gram capacity of the negative electrode active material is ≥355mAh / g. In some embodiments of the present application, the gram capacity of the negative electrode active material is 355mAh / g to 370mAh / g. In some embodiments of the present application, the gram capacity of the negative electrode active material can be 358mAh / g, 360mAh / g, 362mAh / g, 365mAh / g, 368mAh / g, 370mAh / g and any value therebetween.

[0037] According to some embodiments of the present application, the ratio of the diffraction peak area C004 of the 004 crystal plane of the negative electrode active material measured by X-ray diffraction to the diffraction peak area C110 of the 110 crystal plane satisfies 10≤C004 / C110≤40, for example, C004 / C110 can be 12, 15, 17, 20, 23, 25, 28, 30, 33, 35, 37, 39 and any value therebetween. The C004 / C110 of the negative electrode active material is within the above range, which is more conducive to the insertion and extraction of lithium ions.

[0038] According to some embodiments of the present application, the compaction density of the negative electrode active material is ≥1.90 g / cm 3 In some embodiments, the compaction density of the negative electrode active material is a powder compaction density. In some embodiments, the compaction density of the negative electrode active material under a test pressure of 5 t is ≥ 1.90 g / cm 3 The compaction density of the negative electrode active material is related to the pressure that the negative electrode material can withstand after being prepared into the negative electrode. Materials with high compaction density are conducive to the preparation of batteries with high volumetric energy density.

[0039] According to some embodiments of the present application, the negative electrode active material includes artificial graphite. In some embodiments, the artificial graphite includes at least one of needle coke artificial graphite, petroleum coke artificial graphite or asphalt artificial graphite. In some embodiments, at least a portion of the surface of the negative electrode active material contains an amorphous carbon layer. In some embodiments, the raw material of the artificial graphite includes at least one of needle coke, petroleum coke and asphalt, and the raw material is crushed to a certain particle size and then subjected to graphitization treatment at a temperature greater than or equal to 2800°C to obtain the artificial graphite.

[0040] 2. Negative electrode

[0041] The present application provides a negative electrode, which includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes the negative electrode active material described in the first aspect.

[0042] According to some embodiments of the present application, the negative electrode comprises negative electrode active material particles whose angle θ between the long diameter direction and the negative electrode current collector satisfies 45°≤θ≤90°. In some embodiments, the negative electrode active material comprises particles whose angle θ between the long diameter direction and the negative electrode current collector satisfies 50°≤θ≤90°. In some embodiments, the angle θ is 45°, 50°, 55°, 60°, 65°, 70°, 80°, 85°, 90° and any value therebetween. The angle θ described in the present application is an acute angle or a right angle between the long diameter direction of the particle and the negative electrode current collector, such as Figure 1 As shown, the angle distribution can be measured by polarizing microscopy.

[0043] In some embodiments of the present application, the negative electrode comprises negative electrode active material particles whose angle θ between the long diameter direction and the negative electrode current collector satisfies 50°≤θ≤85°. In some embodiments of the present application, the negative electrode comprises negative electrode active material particles whose angle θ between the long diameter direction and the negative electrode current collector satisfies 55°≤θ≤85°.

[0044] According to some embodiments of the present application, in the negative electrode, the angle θ between the long axis direction of the negative electrode active material particles and the negative electrode current collector satisfies 45°≤θ≤90°. In some embodiments, the angle θ between the long axis direction of at least 50% of the negative electrode active material particles in the negative electrode and the negative electrode current collector satisfies 45°≤θ≤90°, for example, the angle θ between the long axis direction of at least 60%, at least 70%, at least 80% or at least 90% of the negative electrode active material particles and the negative electrode current collector satisfies 45°≤θ≤90°.

[0045] According to some embodiments of the present application, in the negative electrode, the angle θ between the long axis direction of the negative electrode active material particles and the negative electrode current collector satisfies 50°≤θ≤85°. According to some embodiments of the present application, in the negative electrode, the angle θ between the long axis direction of the negative electrode active material and the negative electrode current collector satisfies 55°≤θ≤85°. According to some embodiments of the present application, in the negative electrode, the angle θ between the long axis direction of the negative electrode active material and the negative electrode current collector satisfies 65°≤θ≤90°. In some implementations, in the negative electrode, the angle θ between the long axis direction of the negative electrode active material particles and the current collector is 90°, that is, the long axis direction of the negative electrode active material is perpendicular to the current collector.

[0046] The negative electrode active material particles are stacked layer by layer on the current collector surface in different orientations with a certain porosity between the particles to form a negative electrode active material layer. When preparing the negative electrode by conventional processes, the elongated particles tend to have their long sides parallel to the current collector and their short sides perpendicular to the current collector. Such a distribution makes it difficult for lithium ions to pass through the gaps between the particles and embed. According to some embodiments of the present application, in the negative electrode of the present application, the negative electrode active material particles are as follows: Figure 1 As shown in the figure, the long diameter is arranged on the current collector at a certain angle, and the angle of arrangement is ≥45°. In this way, the path of lithium ions being embedded in the graphite layer is greatly shortened during the lithium insertion process, which can effectively increase the lithium insertion speed of lithium ions. At the same time, during the lithium insertion process, since the angle between the long diameter and the current collector is ≥45°, Figure 2 As shown, lithium ions are embedded into the negative electrode active material layer from the short axis direction, so the expansion perpendicular to the negative electrode direction is greatly reduced.

[0047] According to some embodiments of the present application, the ratio of the diffraction peak area C004 of the 004 crystal plane of the negative electrode measured by X-ray diffraction to the diffraction peak area C110 of the 110 crystal plane satisfies C004 / C110≤15, for example, C004 / C110 can be 5, 7, 8, 9, 10, 11, 12, 13, 14, 15 and any value therebetween. The C004 / C110 of the negative electrode is more conducive to the insertion and extraction of lithium ions within the above range. In some embodiments of the present application, the C004 / C110 of the negative electrode is less than the C004 / C110 of the negative electrode active material. In the present application, the long diameter particles are made to be at an angle of 45° to 90° with the direction parallel to the current collector by a special method, so that the ratio of C004 / C110 of the negative electrode becomes smaller, which is more conducive to the extraction and extraction of lithium ions.

[0048] According to some embodiments of the present application, the electrolyte has good wettability in the negative electrode, satisfying a wettability time of ≤2 min.

[0049] According to some embodiments of the present application, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer is disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes any one of the aforementioned negative electrode active materials.

[0050] In some embodiments, the negative electrode active material layer also includes a binder, which includes one or more of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene, styrene-butadiene rubber, acrylate and epoxy resin.

[0051] In some embodiments, the negative electrode further comprises a conductive coating between the negative electrode active material layer and the current collector, wherein the conductive coating comprises one or more of a conductive agent such as carbon fiber, Ketjen black, acetylene black, carbon nanotubes, and graphene. In some embodiments, the current collector of the negative electrode may comprise at least one of copper foil, aluminum foil, nickel foil, or a carbon-based current collector.

[0052] According to some embodiments of the present application, the method for preparing the negative electrode of the present application includes applying a slurry containing a negative electrode active material to a current collector in the presence of a magnetic field. In some embodiments of the present application, the method includes applying a slurry containing a negative electrode active material to a current collector in the presence of a magnetic field, so that the angle θ between the long axis direction of the negative electrode active material and the negative electrode current collector satisfies 45°≤θ≤85°. In some embodiments, the magnetic induction intensity of the magnetic field is 3000Gs to 7200Gs.

[0053] In some embodiments, by utilizing the reverse magnetic properties of graphite, a certain amount of magnetic induction intensity is applied when the negative electrode slurry is coated on the current collector, for example, the intensity is 3000Gs to 7200Gs, and the negative electrode active material particles treated with the magnetic induction intensity can be arranged on the current collector in a manner such that the short diameter is parallel to the current collector and the long diameter is perpendicular to the current collector. This treatment can effectively arrange the lithium insertion end face of the negative electrode active material such as graphite in a direction parallel to the current collector, thereby increasing the lithium insertion speed of lithium ions.

[0054] 3. Secondary battery

[0055] The secondary battery pack of the present application is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery. In some embodiments, the secondary battery of the present application includes a positive electrode, the negative electrode described in the second aspect, a separator and an electrolyte.

[0056] In some embodiments, the secondary battery is disassembled at 50% SOC to obtain a negative electrode plate, and the thickness of the negative electrode plate is measured using a micrometer. To ensure the representativeness of the measurement, 14 points are tested and the average value is taken. Compared with the negative electrode plate in an uncharged state, the increase rate of the thickness of the negative electrode plate is ≤15%.

[0057] In some embodiments, the battery thickness measured after the secondary battery is cycled 50 times is compared with the battery thickness tested at 50% SOC, and the increase in the battery thickness is ≤5%, and the battery thickness is measured using a micrometer.

[0058] In some embodiments, the secondary battery has a capacity ratio retention rate of ≥90% when charged at 5C and 0.5C at 25°C.

[0059] 1. Negative electrode

[0060] The negative electrode in the secondary battery of the present application includes the negative electrode described in the second aspect.

[0061] 2. Positive electrode

[0062] The materials, compositions and manufacturing methods of the positive electrode that can be used in the embodiments of the present application include any technology disclosed in the prior art.

[0063] According to some embodiments of the present application, the positive electrode includes a current collector and a positive electrode active material layer located on the current collector. According to some embodiments of the present application, the positive electrode active material includes, but is not limited to: lithium cobalt oxide (LiCoO 2 ), lithium nickel cobalt manganese (NCM) ternary materials, lithium iron phosphate (LiFePO 4 ) or lithium manganate (LiMn 2 O 4 ).

[0064] According to some embodiments of the present application, the positive electrode active material layer also includes a binder and optionally includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.

[0065] According to some embodiments of the present application, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0066] According to some embodiments of the present application, the current collector may include, but is not limited to: aluminum foil.

[0067] 3. Electrolyte

[0068] The electrolyte that can be used in the embodiments of the present application can be an electrolyte known in the prior art.

[0069] In some embodiments, the electrolyte includes an organic solvent, a lithium salt and an additive. The organic solvent of the electrolyte according to the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art that can be used as an electrolyte additive.

[0070] In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propyl propionate or ethyl propionate.

[0071] In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 ), bis(trifluoromethanesulfonyl)imide lithium LiN (CF 3 SO2 ) 2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI), LiB(C 2 O 4 ) 2 (LiBOB) or lithium difluorooxalatoborate LiBF 2 (C 2 O 4 )(LiDFOB).

[0072] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5 mol / L to 3 mol / L, 0.5 mol / L to 2 mol / L, or 0.8 mol / L to 1.5 mol / L.

[0073] In some embodiments, the additives include, but are not limited to: vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 1,3-propane sultone (PS), diethylene sulfate (DTD), 1,3-dioxane, maleic anhydride, adiponitrile, succinonitrile, 1,3,5-pentanetrinitrile, 1,3,6-hexanetrinitrile.

[0074] 4. Isolation film

[0075] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0076] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0077] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0078] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0079] The polymer layer contains polymers, and the polymer material is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0080] 4. Electronic Devices

[0081] The present application further provides an electronic device, which includes the secondary battery described in the third aspect of the present application.

[0082] The electronic device or device of the present application is not particularly limited. In some embodiments, the electronic device of the present application includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0083] Example

[0084] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0085] 1. Preparation of lithium-ion batteries

[0086] 1. Preparation of negative electrode

[0087] The negative electrode active materials graphite, styrene butadiene rubber (abbreviated as SBR) and sodium carboxymethyl cellulose (abbreviated as CMC) are fully stirred and mixed in a deionized water solvent according to a weight ratio of 95:2:3 to form a uniform negative electrode slurry; the slurry is coated on a current collector copper foil pre-coated with a primer (such as carbon black), the thickness of the primer is 1.5 μm to 3 μm, and the coating weight of the negative electrode slurry is X mg / mm 2 (Coating weight is 0.032mg / mm2 Up to 0.120mg / mm 2 , for example 0.032 mg / mm 2 , 0.055mg / mm 2 、0.070mg / mm 2 、0.090mg / mm 2 、0.120mg / mm 2 ), the double-sided coating thickness of the negative electrode slurry is Yμm (the coating thickness is between 70μm and 150μm, such as 70μm, 90μm, 110μm, 130μm, 150μm), and a certain magnetic flux is applied during the coating process to change the arrangement of particles on the current collector, and the applied magnetic flux size is 3000Gs to 7200Gs. After drying, cold pressing, cutting, and welding the pole ears to obtain the negative electrode, also known as the negative pole sheet.

[0088] The preparation method of graphite is as follows:

[0089] (1) using a high-efficiency pulverizing device to pulverize graphite precursor (selecting raw materials with strong needle-like properties) into particles with a certain particle size, and then sending the pulverized particles into a classification device, and controlling the particle size of the particles within a certain range through the centrifugal separation effect of the device, and then sending the pulverized particles into a graphitization furnace for graphitization. The graphitization equipment can be any one of an Acheson furnace, an inner-tandem graphitization furnace, and a continuous graphitization furnace. The material entering the graphitization furnace is crushed into a desired particle size (Dv50 is 6 μm to 10 μm); and

[0090] (2) Graphitizing at 2800°C to 3200°C, collecting the desired graphite after graphitization. The graphite parameters are adjusted by controlling the precursor particle size and the graphitization temperature.

[0091] The aspect ratio of the negative electrode active material graphite is controlled in the following manner: during the preparation of the negative electrode active material graphite, the prepared graphite is fed into the shaping zone through a feeding system for grinding, so that the particle surface has edges and corners, thereby controlling the aspect ratio and sphericity of the particles. Subsequently, the ground particles are graded through a self-dividing classification zone to obtain particles with a desired distribution.

[0092] 2. Preparation of positive electrode

[0093] LiCoO 2 ), acetylene black and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent at a weight ratio of 96:2:2 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried, cold pressed, cut and slit to obtain the positive electrode.

[0094] 3. Preparation of electrolyte

[0095] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC) were mixed in a mass ratio of 3:4:3, and then fully dried lithium salt LiPF 6 The electrolyte is prepared by dissolving the above-mentioned non-aqueous solvent, and finally adding 3 wt % of fluoroethylene carbonate, 2 wt % of 1,3-propane sultone and 2 wt % of succinonitrile.

[0096] 4. Preparation of isolation membrane

[0097] A 7 μm thick polyethylene (PE) porous polymer film was used as the isolation membrane.

[0098] 5. Preparation of lithium-ion batteries

[0099] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is placed between the positive electrode and the negative electrode to play an isolating role, and then they are wound to obtain a bare cell; after welding the pole ears, the bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery is obtained.

[0100] 2. Test Method

[0101] 1. Test method for aspect ratio distribution of negative electrode active materials

[0102] The aspect ratio distribution of the negative electrode active material was tested using a Sympatec QICPIC dynamic particle image analyzer.

[0103] 2. Test method for compaction density of negative electrode active materials

[0104] The test standard refers to GB / T 24533-2009 "Graphite Negative Electrode Materials for Lithium-ion Batteries". The specific test method is to weigh 1.0000±0.0500g of the sample and place it in the test mold (CARVER#3619 (13mm), and then place the sample in the test equipment. The test equipment is Sansi Zongheng UTM7305, with a test tonnage of 0.3t to 5.0t. The compaction density in this application is the compaction density measured at 5t. The calculation formula of compaction density is: compaction density = mass of negative electrode active material / force-bearing area of ​​negative electrode active material / thickness of sample.

[0105] 3. Test method for the angle between the long diameter of the particles in the negative electrode and the current collector

[0106] Negative ion milling (CP) sample preparation process:

[0107] The above negative electrode sheet was cut into a size of 0.5 cm × 1 cm, and the cut negative electrode sheet was pasted on a 1 cm × 1.5 cm silicon wafer carrier using conductive glue, and then one end of the negative electrode sheet was processed using argon ion polishing (parameters: 8KV acceleration voltage, 4h for each sample) to obtain a negative electrode CP sample. Argon ion polishing uses a high-voltage electric field to ionize argon gas to produce an ion state. The generated argon ions bombard the surface of the negative electrode sheet at high speed under the action of the acceleration voltage, and the negative electrode sheet is eroded layer by layer to achieve the polishing effect.

[0108] After the negative electrode CP sample was prepared, it was analyzed using a polarizing microscope.

[0109] Polarizing microscope operation is as follows:

[0110] Image acquisition process: An Axio imager upright microscope (manufactured by Carl Zeiss AG, Imagine A2) was used for image acquisition. An AxioCam MRc5 digital camera was connected to the polarized light microscope with a connector. Polarized light microscope images were taken with a shutter time of 1.6 seconds. The images captured by the digital camera were automatically transferred to a computer.

[0111] Image analysis process: Select an image of 1200 pixels × 1600 pixels as the analysis object (equivalent to a field of view of 480μm × 540μm). Use the Multiphase software that comes with AxioVision for analysis. After importing the collected photos into the software, click on a point of a certain orientation on the image, and all areas with the same grayscale value and color value as the measured object will be selected immediately; use the same method to select points of other orientations to obtain areas of different orientations and colors. Using AxioVision's automatic calculation software (Axio Vision SE64 Rel.4.9), measure the data of different particle angles in the image and the proportion of different angles, and obtain the long diameter of the negative electrode active material particles based on the measured results.

[0112] 4. Test method for particle size of negative electrode active materials (Dv50 and Dv99)

[0113] The particle size test method refers to GB / T 19077-2016. The specific process is to weigh 1g of the sample and mix it evenly with 20mL of deionized water and a trace amount of dispersant. After placing it in an ultrasonic device for 5 minutes, the solution is poured into the sampling system Hydro 2000SM for testing. The test equipment used is the Mastersizer 3000 produced by Malvern. During the test, when the laser beam passes through the dispersed particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The data is then used to analyze and calculate the particle size distribution that forms the scattering spectrum. The refractive index of the particles used in the test is 1.8. One sample is tested three times, and the particle size is finally taken as the average of the three tests.

[0114] 5. C004 / C110 test method for negative electrode active material layer

[0115] The (004) plane diffraction line pattern and (110) plane diffraction line pattern in the X-ray diffraction spectrum of the negative electrode active material layer were tested in accordance with the mechanical industry standard JB / T 4220-2011 "Method for Determination of Lattice Parameters of Artificial Graphite" of the People's Republic of China. The test conditions are as follows: X-rays are radiated by CuKα, and CuKα radiation is removed by a filter or a monochromator. The operating voltage of the X-ray tube is 30kV to 35kV, and the operating current is 15mA to 20mA. The scanning speed of the counter is 1 / 4(°) / min. When recording the 004 diffraction line pattern, the scanning range of the diffraction angle 2θ is 53° to 57°. When recording the 110 diffraction line pattern, the scanning range of the diffraction angle 2θ is 75° to 79°. The peak area obtained from the (004) plane diffraction line pattern is recorded as C004. The peak area obtained from the (110) plane diffraction line pattern is recorded as C110. Calculate the C004 / C110 ratio of the negative electrode active material layer. The C004 / C110 test method for the negative electrode active material is the same as the C004 / C110 test method for the negative electrode, the only difference is that the negative electrode active material needs to be first placed in a glass sheet with a groove and compacted, and then replace the negative electrode.

[0116] 6. Test method for porosity of negative electrode active material layer

[0117] The negative electrode active material layer samples were prepared into complete round pieces. Thirty samples were tested for each embodiment or comparative example, and the volume of each sample was about 0.35 cm 3 The porosity of the negative electrode active material layer was tested according to the standard "GB / T24586-2009 Determination of apparent density, true density and porosity of iron ore".

[0118] 7. Test method for negative electrode wetting time

[0119] Take a negative electrode sample prepared in the embodiment or comparative example with a length of 50 mm and a width of 50 mm. Under dry conditions, take 5 mL of the electrolyte prepared in the above "Preparation of electrolyte" and drop it on the sample surface, and start timing. When the electrolyte droplets on the sample surface disappear, stop timing. The timing time is recorded as the wetting time of the negative electrode. Test 30 samples for each embodiment or comparative example and take the average value.

[0120] Or, after discharging the battery at 0.1C until the voltage reaches 3V, disassemble the battery, take out the negative electrode, dry it at 70°C, cut the obtained negative electrode sheet into samples with a length of 50 mm and a width of 50 mm, and drop 5 mL of the electrolyte used in the embodiment or comparative example on the surface of the sample under dry conditions, and start timing. When the electrolyte droplets on the surface of the sample disappear, stop timing. The timing time is recorded as the wetting time of the negative electrode. Test 30 samples for each embodiment or comparative example, and take the average value.

[0121] 8. Test method for lithium ion liquid phase transfer impedance (Rion)

[0122] The lithium-ion battery was connected to the Bio-Logic VMP3B electrochemical workstation produced by Bio-LogiC for testing, with a frequency range of 30mHz to 50kHz and an amplitude of 5mV. After data collection, the impedance complex plane diagram was used to analyze the data and obtain the lithium ion liquid phase transfer impedance (Rion).

[0123] 9. Test method for 5C discharge capacity retention rate of lithium-ion batteries

[0124] After the lithium-ion battery is left at rest for 5 minutes at 25°C, it is charged to 4.45V at a constant current of 0.7C, then charged to 0.05C at a constant voltage of 4.45V, left to rest for 5 minutes, and then discharged to 3.0V at a constant current of 0.5C, and left to rest for 5 minutes. Repeat the above charge and discharge process, discharge at 0.1C, record the 0.1C discharge capacity of the lithium-ion battery, then discharge at 5C, record the 5C discharge capacity of the lithium-ion battery. The 5C discharge capacity retention rate of the lithium-ion battery is calculated by the following formula:

[0125] 5C discharge capacity retention rate = 5C discharge capacity / 0.1C discharge capacity × 100%.

[0126] 10. Test method for DC resistance (DCR) of lithium-ion batteries

[0127] At 25°C, charge the lithium-ion battery to 4.45V at 1.5C constant current, then charge to 0.05C at 4.45V constant voltage, and let it stand for 30 minutes. Discharge at 0.1C for 10 seconds, record the voltage value as U1, discharge at 1C for 360 seconds, record the voltage value as U2. Repeat the charge and discharge steps 5 times. "1C" is the current value that completely discharges the capacity of the lithium-ion battery within 1 hour.

[0128] The DC resistance R of a lithium-ion battery at 25°C is calculated by the following formula:

[0129] R = (U2-U1) / (1C-0.1C).

[0130] The DC resistance of lithium-ion batteries at 0°C is tested using basically the same method, the only difference being that the operating temperature is 0°C.

[0131] Unless otherwise specified, the DCR described in this application refers to the direct current resistance of a lithium-ion battery at a state of charge (SOC) of 10%.

[0132] 11. Method for determining lithium deposition in lithium-ion batteries

[0133] Take the lithium-ion battery under test and place it at 0℃ for 5 minutes, charge it to 4.45V at 0.8C constant current, and then charge it to 0.05C at 4.45V constant voltage; let it stand for 5 minutes, then discharge it to 3.0V at 0.5C constant current, and let it stand for 5 minutes. After repeating the above charging and discharging process 10 times, fully charge the battery, disassemble it in a dry room, and take photos to record the state of the negative electrode.

[0134] The degree of lithium plating of lithium-ion batteries is determined according to the following standards:

[0135] When the disassembled negative electrode appears golden yellow as a whole, with a very small part being observed to be gray, and the area of ​​the gray area is <2%, it is determined that no lithium is deposited.

[0136] When most of the negative electrode after disassembly is golden yellow, and gray can be observed in some positions; and the area of ​​the gray area is between 2% and 20%, it is judged to be slight lithium deposition.

[0137] When the disassembled negative electrode appears gray as a whole, with golden color observed in some locations, and the area of ​​the gray area is between 20% and 60%, it is judged to be lithium deposition.

[0138] When the disassembled negative electrode is gray as a whole and the area of ​​the gray region is greater than 60%, it is determined to be severe lithium deposition.

[0139] 12. Test method for charge transfer impedance (Rct) of lithium-ion batteries

[0140] In the above process of preparing the lithium-ion battery, a copper wire was additionally connected as a reference electrode, and lithium was plated on the negative electrode at a current of 20 μA for 6 hours to obtain a three-electrode lithium-ion battery.

[0141] The three-electrode lithium-ion battery was connected to the Bio-Logic VMP3B electrochemical workstation produced by Bio-LogiC, France, for testing, with a frequency range of 30mHz to 50kHz and an amplitude of 5mV. After collecting the data, the impedance complex plane diagram was used to analyze the data and obtain the charge transfer impedance (Rct) of the lithium-ion battery.

[0142] 13. Test method for thickness growth rate of negative electrode sheet along Z direction

[0143] Test the thickness of the negative electrode after cold pressing treatment, recorded as T1. The treated negative electrode is made into a lithium-ion battery according to the preparation steps of lithium-ion batteries. The lithium-ion battery is left to stand at 25°C for 5 minutes and then charged to 3.95V (i.e., 50% SOC) at a constant current of 0.7C. Disassemble the lithium-ion battery under dry conditions to obtain the disassembled negative electrode. Record the thickness of the negative electrode at least 14 points, take the average value, and record it as T2. Calculate the expansion rate of the negative electrode along the Z direction by the following formula:

[0144] Expansion rate in Z direction = (T2 - T1) / T1 x 100%.

[0145] 14. Battery expansion rate in the Z-axis direction

[0146] After the lithium-ion battery is left at rest for 5 minutes at 45°C, it is charged to 4.45V at a constant current of 0.7C, and then charged to 0.05C at a constant voltage of 4.45V and left to rest for 5 minutes. The thickness of the lithium-ion battery at three locations is tested by the MMC test method, and the average value is recorded as MMC. 0 Then the lithium-ion battery was discharged at a constant current of 0.5C to 3.0V and left to stand for 5 minutes. The above charge and discharge cycle was repeated 50 times and recorded as MMC 50 (50 represents the number of cycles).

[0147] The cycle expansion rate of lithium-ion batteries at 45°C is calculated by the following formula:

[0148] Cycle expansion ratio (45℃) = (MMC x -MMC 0 ) / MMC 0 ×100%.

[0149] The MMC test method as described above is: use a micrometer tester (manufactured by Mitutoyo, Japan, model: MDC-25SX) to measure the thickness of the lithium-ion battery near the negative electrode tab, measure three different positions for each sample, take the average value, and record it as the MMC thickness.

[0150] 3. Test Results

[0151] Table 1 shows the effect of the aspect ratio distribution of graphite particles, the magnitude of the magnetic flux applied during the coating process on the gram capacity, graphite particle powder C004 / C110, negative electrode sheet C004 / C110, the angle between the major axis of the particles and the current collector, the growth rate of the thickness of the negative electrode sheet in the Z-axis direction, and the direct current resistance (DCR) of the lithium ion battery 1. The negative active materials used in Examples 1 to 26 are all made of the same raw material, which is needle coke, obtained by sintering at 3000°C, and the Dv50 of the negative active material particles is 8μm and the Dv99 is 27μm.

[0152] Table 1

[0153]

[0154]

[0155] Note: The angle θ is the angle between the long axis of the negative electrode active material particles and the current collector. The measured angle value is the average value of the angles of all particles.

[0156] As shown in Table 1, from Example 1 to Example 26, as the aspect ratio of the negative electrode active material particles increases, the gram capacity gradually decreases, and the powder C004 / C110 also gradually decreases. The smaller the aspect ratio, the greater the magnetic flux required. This is because the morphology of particles with a small aspect ratio is as follows Figure 1 As shown, the particles are in the shape of long strips, and for the long strip particles, the particles tend to be arranged parallel to the direction of the current collector when they are piled up on the negative electrode sheet during coating. When the long side of the particles on the negative electrode sheet is parallel to the current collector, the lithium ions need to travel a longer path to be embedded in the graphite layer during the process of lithium extraction. During the coating process, a certain amount of magnetic flux is applied to the negative electrode sheet, and the graphite particles will adjust their arrangement direction due to the presence of the magnetic field by utilizing the reverse magnetism of the graphite itself. By controlling the size of the applied magnetic field to control the arrangement of the graphite particles on the negative electrode sheet, the negative electrode sheet C004 / C110 is smaller than the powder.

[0157] It can be seen from the data of Examples 1 to 6, 7 to 9, 10 to 12, 13 to 18, and 19 to 24 that when the AR of the negative electrode active material particles 90 When the size of AR is fixed, 10 With the increase of AR 50 The increase of the powder C004 / C110 value is affected because the particle AR 10 Increase or AR 50The increase indicates that the morphology of the particles tends to be spherical, so the C004 / C110 of the powder measured by XRD changes. At the negative electrode sheet level, due to the introduction of a magnetic field during the coating process, the change pattern of the C004 / C110 of the negative electrode sheet also changes with the AR 10 and AR 50 The expansion changes will affect the C004 / C110 changes of the negative electrode sheet.

[0158] As shown in Example 23 and Example 24, when the applied magnetic field is the same, AR 10 For larger materials, the angle between the particle's long diameter and the current collector's direction is larger, which means that more long diameters are arranged perpendicular to the current collector's direction. This can effectively shorten the lithium ion transfer path and reduce the expansion of the negative electrode sheet. Therefore, the thickness growth rate of the negative electrode sheet is significantly reduced.

[0159] Compared with Example 24 and Example 25, the AR of the negative electrode active material particles of Example 25 is 90 Under the same magnetic flux conditions, the angle between the particle length and the current collector of Example 25 is reduced. This is because when the proportion of spherical particles is too large, the arrangement of the particles changes after applying a certain magnetic flux, but the change is very small. Similarly, as shown in Comparative Example 1, the AR of the negative electrode active material particles 10 It is only 0.05, indicating that some particles are very elongated in shape, so a very large magnetic field is required to control the C004 / C110 ratio within a certain range.

[0160] It can be seen from Comparative Example 2 that the AR of the negative electrode active material particles of Comparative Example 2 10 , A.R. 50 and AR 90 The particles are relatively large and the morphology of the particles is relatively round, so the required magnetic flux is very small. However, the specific capacity of the material is also very low. The present application targets graphite with strong needle-like properties and high specific capacity. After controlling its aspect ratio within a certain range, the required magnetic flux is applied to it and its arrangement on the negative electrode plate is adjusted to obtain high energy density while controlling the expansion of the negative electrode plate.

[0161] Table 2 shows the effects of different width-length and particle size ratios of the particles on the powder C004 / C110, the negative electrode sheet C004 / C110 and the battery performance when the coated negative electrode sheet is treated with a magnetic flux of 5000 Gs under different particle size conditions.

[0162] Table 2

[0163]

[0164] Note: The angle θ is the angle between the long axis of the negative electrode particle and the current collector. The measured angle value is the average value of the angles of all particles.

[0165] As shown in Examples 27 and 30, and Examples 28 and 29, for negative electrode active materials with the same particle size distribution and different aspect ratios, when the aspect ratio is larger, the powder C004 / C110 is smaller, and under the same magnetic flux conditions, the smaller the C004 / C110 of the negative electrode pole piece, the larger the angle between the long diameter of the negative electrode active material particles and the current collector, and the feedback to the battery performance is that the battery expands less along the Z axis. This is because particles with a large aspect ratio are more rounded and are easier to rotate to be arranged perpendicular to the current collector under a magnetic field.

[0166] As shown in Example 30 and Example 31, the aspect ratios of the particles are similar, but the particle size distributions of the particles are different. The larger the particle size distribution, the larger the powder C004 / C110, and therefore the negative electrode plate C004 / C110 is large. The corresponding battery performance is a large expansion growth rate along the Z axis.

[0167] The width-to-length ratio AR of the negative electrode active material particles of Comparative Example 3 10 Under a certain magnetic flux, the pole piece C004 / C110 is still large, so the battery expands greatly along the Z axis, and because the major diameter of some particles is too long, it is not conducive to the deintercalation of lithium ions, so lithium is easily deposited under certain rate conditions.

[0168] Table 3 shows the effect of different aspect ratios of particles on battery performance when the coated negative electrode piece is treated with a magnetic flux of 5000Gs.

[0169] Table 3

[0170]

[0171] As shown in Examples 39 to 43, the larger the aspect ratio of the material, the greater the porosity of the prepared negative electrode active material layer under the same magnetic flux treatment conditions, so the electrolyte infiltration time of the negative electrode plate is shortened. At the same time, the aspect ratio of the negative electrode active material increases, the lithium ion transfer impedance (Rion), charge transfer impedance (Rct) and direct current resistance (DCR) of the lithium ion battery containing the material decrease, and the greater the discharge capacity retention rate at the 5C rate. For Example 45, the aspect ratio of its negative electrode active material is the smallest, so under the same magnetic flux treatment conditions, since some particles are still arranged parallel to the current collector, the porosity of the negative electrode active material layer is small, the electrolyte enters the negative electrode plate for a long time, and the impedance of lithium ions passing through the graphite particles and embedded in the graphite layer is also large. Therefore, in the actual application process, it is necessary to simultaneously regulate the magnetic flux and the aspect ratio of the particles and the particle size of the particles in order to achieve the best performance.

Claims

1. A secondary battery comprising a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material, wherein the particles of the negative electrode active material satisfy the following relationship: 0.1≤AR 10 <0.2,0.2≤AR 50 <0.4,0.4≤AR 90 ≤0.8, in, When the particle volume cumulative distribution is 10%, the width-to-length ratio of the negative electrode active material is AR 10 When the particle volume cumulative distribution is 50%, the width-to-length ratio of the negative electrode active material is AR 50 When the particle volume cumulative distribution is 90%, the width-to-length ratio of the negative electrode active material is AR 90 ; The negative electrode active material comprises artificial graphite; An angle θ between the major axis direction of the particles of the negative electrode active material and the direction parallel to the negative electrode current collector satisfies 45°≤θ≤90°.

2. The secondary battery according to claim 1, wherein 1.3<ON 90 / ON 50 <3.5。 3. The secondary battery according to claim 1, wherein The negative electrode active material satisfies at least one of the conditions (a) to (d): (a) the negative electrode active material satisfies 1.5≤Dv99 / Dv50≤4.5; (b) The gram capacity of the negative electrode active material is ≥355 mAh / g; (c) the ratio of the diffraction peak area C004 of the (004) crystal plane to the diffraction peak area C110 of the (110) crystal plane of the negative electrode active material satisfies 10≤C004 / C110≤40; (d) The compaction density of the negative electrode active material is ≥ 1.90 g / cm 3 .

4. The secondary battery according to claim 1, wherein The artificial graphite comprises at least one of needle coke artificial graphite, petroleum coke artificial graphite or pitch artificial graphite.

5. The secondary battery according to any one of claims 1 to 4, wherein The negative electrode active material satisfies at least one of the conditions (1) to (3): (1)1.5≤AR 90 / AR 50 ≤3; (2)2≤Dv99 / Dv50≤4; (3) The ratio of the diffraction peak area C004 of the (004) crystal plane to the diffraction peak area C110 of the (110) crystal plane of the negative electrode active material satisfies 10≤C004 / C110≤30. 6 . The secondary battery according to claim 1 , further comprising a positive electrode, a separator and an electrolyte.

7. The secondary battery according to claim 6, wherein The ratio of the diffraction peak area C004 of the (004) crystal plane to the diffraction peak area C110 of the (110) crystal plane of the negative electrode satisfies C004 / C110≤15.

8. The secondary battery according to claim 6, wherein The electrolyte infiltration time of the negative electrode is ≤2min.

9. The secondary battery according to claim 6, wherein The negative electrode satisfies at least one of the conditions (4) and (5): (4) The negative electrode comprises particles of negative electrode active material whose angle θ between the long axis direction and the direction parallel to the negative electrode current collector satisfies 55°≤θ≤85°; (5) The ratio of the diffraction peak area C004 of the (004) crystal plane to the diffraction peak area C110 of the (110) crystal plane of the negative electrode satisfies C004 / C110≤13. 10 . An electronic device comprising the secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Immunogenic Compositions

    AR105010A1

  • MULTI-SPEED DRILL BIT ASSEMBLY

    AR105090A1

  • Negative electrode for nonaqueous electrolyte secondary battery, method for producing same, and nonaqueous electrolyte secondary battery

    CN102484244A

  • Negative electrode active material, and electrochemical device using same and electronic device

    CN112689919A